Asbestos Related non-Malignant Pleural Disease and Mesothelioma - Musk, B.; de Klerk, N.; Brims, Fraser (CRC Press, 2016)
It also covers related long-term conditions, such as asthma and COPD. This edition has been completely revised and brought up to date for all physicians dealing with pulmonary disorders caused by the environment or the workplace.